Synthesis, characterization and anti-bacterial studies or Hydrazide Schiff bases of Acetylacetonate metal complexes - Dikio, Charity Wokwu (My University, 2014)
Infectious diseases, a group of illnesses caused by specific pathogens or its toxins is a leading cause of death globally. Treatment with antibiotics is a key intervention in the control and management of many infectious disease. However, the increasing incidence of antibiotics failure, due to the emergence of drug resistant pathogens, is rendering the use of antibiotics chemotherapy ineffective. A possible solution is to synthesize new compounds with broad spectrum characteristics and superior drug performances as alternative to conventional antibiotics. Schiff Bases are biologically active ligands. They form metal complexes with superior biological activities. This research aims to synthesize some Schiff Base metal complexes and investigate their biological effects on Staphylococcus aureus and Enterococcus faecalis. Metal acetylacetonates of Vanadium, Copper, Cobalt, Zinc, Magnesium, Manganese, Cadmium, Nickel and Iron were synthesized and characterized by Fourier transform infrared spectroscopy. Four Schiff bases, LI, L2, L3 and L4 were also synthesized by the condensation of 4- (diethylamino)-2-hydroxybenzaldehyde with 4-nitrobenzohydrazide and 4-methoxybenzohydrazide to form L1 and L2. 4-(dimethylamino) benzaldehyde was reacted with 4-nitrobenzohydrazide and 4-methoxybenzohydrazide to form L3 and L4 respectively. The Schiff base ligands were then reacted with synthesized Vanadium, manganese, cobalt and magnesium acetylacetonates to form Schiff base complexes (SBC 1A to 4D). Schiff bases ligands and complexes were characterized by FT-IR, 1H-NMR, 13C-NMR, TGA and DTA. Fourier Transform infrared spectroscopy (FTIR) of the acetylacetonates showed the formation of metal acetylacetonates as characterized by the absence of the carbonyl stretching n(C=O) vibration in metal acetylacetonate spectra as compared to pure acetylacetone. Metal acetylacetonates also showed the presence of metal oxygen vibration frequency, n(M-O-C), in the spectra obtained. Thermogravimetric analysis (TGA) and Derivative or Differential Thermogravimetric analysis (DTA) of the Schiff base ligands showed the presence of a single decomposition product in L1, L2, L3 and L4 indicating the formation of a single reaction product while those of Schiff base complexes showed the formation of several decomposition products. Proton and carbon thirteen Nuclear Magnetic Resonance (1H- and 13C-NMR) spectroscopy of the Schiff base ligands indicated the presence of hydrogen and carbon-13 in different environments. The chemical shifts of the hydrogens and carbon-13 provided evidence that Schiff base ligands were formed. The strongest evidence is the presence of the azomethine hydrogen and carbon in the spectra of the Schiff base ligands. The presence of aromatic hydrogens and carbon at chemical shift environments found in literature also confirmed the formation of Schiff base ligand. The NMR spectra of Schiff base complexes showed the presence of azomethine (HC=N) and aromatic hydrogens at expected chemical shifts. The synthesized Schiff bases and their corresponding metal complexes were screened for their invitro antibacterial activities against two Gram-positive (Staphylococcus aureues and Enterococcus feacalis) bacterial strains by the Agar-well diffusion methods.The ligands and complexes were tested against confirmed S. aureus and E. faecalis strains and only 4 exhibited antimicrobial activities. The ligands and complexes were effective against the S. aureusand E. faecalis isolates.
M. Tech. (Chemistry, Department of Chemistry), Vaal University of Technology
Keywords: Infectious diseases; Antibiotics failure; Schiff bases; Staphylococcus aureus; Enterococcus faecalis.; drug resistant pathogens; Metal complexes; 615.7922; Anti-infective agents.; Schiff bases